The perceptions and satisfaction index of Yogyakarta’s citizens on congestion and air pollution - Ristanti, Putri Wulan; Suryanto, Suryanto (Universitas Muhammadiyah Yogyakarta, 2023)
Yogyakarta City is one of Indonesia's most popular tourist destinations. The tourism sector is the highest tax revenue for local government. Besides, tourism gives high revenue but also negatively impacts the citizens as hosts, such as congestion and pollution. This study was conducted to determine the importance level of each attribute on the quality of congestion and air pollution management services in Yogyakarta based on the citizen's perception by utilizing the Importance Performance Analysis (IPA) method. This study also aimed to determine the Yogyakarta citizens' satisfaction level with managing congestion and air pollution using the Customer Satisfaction Index (CSI) method. This study implemented a purposive sampling technique which was then obtained from the population sample of 100 respondents with 86 saturated samples. Based on the perception of the Yogyakarta citizens, The results showed that a high level of attributes included wide and comfortable pavements, trees that block the sunlight and have a cooling effect, motorists who obeyed traffic signs, and drivers who drive well. The Yogyakarta Citizens' satisfaction index result showed 60.54%, which has the category of